2019
DOI: 10.1038/s41398-019-0369-x
|View full text |Cite
|
Sign up to set email alerts
|

A promoter variant in ZNF804A decreasing its expression increases the risk of autism spectrum disorder in the Han Chinese population

Abstract: Synaptic pathology may be one of the cellular substrates underlying autism spectrum disorder (ASD). ZNF804A is a transcription factor that can affect or regulate the expression of many candidate genes involved in ASD. It also localizes at synapses and regulates neuronal and synaptic morphology. So far, few reports have addressed possible associations between ZNF804A polymorphisms and ASD. This study aimed to investigate whether ZNF804A genetic variants contribute to ASD susceptibility and its possible patholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 55 publications
(41 reference statements)
1
7
0
Order By: Relevance
“…Studies have shown that MSUT2 knockout has anti-inflammatory and neuroprotective effects in a mouse model. The flowchart is Frankel et al, 1987;Wolfe et al, 2000;Schefe et al, 2006;Brayer et al, 2008;Town et al, 2009;Fan et al, 2012;Shi et al, 2013;Yuan et al, 2013;Xu et al, 2016;Yu et al, 2017;Brahmachari et al, 2019;Kruszka et al, 2019;Lorsch et al, 2019;Ohkubo et al, 2019;Zhang et al, 2019;Choi et al, 2020;Deshpande et al, 2020;Hu et al, 2020;Xiao et al, 2020;Dentici et shown in Figure 1. Loss of function of MSUT2 can reduce the formation of tau protein and protect the loss of neurons, but the molecular mechanism is still unclear.…”
Section: Alzheimermentioning
confidence: 99%
“…Studies have shown that MSUT2 knockout has anti-inflammatory and neuroprotective effects in a mouse model. The flowchart is Frankel et al, 1987;Wolfe et al, 2000;Schefe et al, 2006;Brayer et al, 2008;Town et al, 2009;Fan et al, 2012;Shi et al, 2013;Yuan et al, 2013;Xu et al, 2016;Yu et al, 2017;Brahmachari et al, 2019;Kruszka et al, 2019;Lorsch et al, 2019;Ohkubo et al, 2019;Zhang et al, 2019;Choi et al, 2020;Deshpande et al, 2020;Hu et al, 2020;Xiao et al, 2020;Dentici et shown in Figure 1. Loss of function of MSUT2 can reduce the formation of tau protein and protect the loss of neurons, but the molecular mechanism is still unclear.…”
Section: Alzheimermentioning
confidence: 99%
“…Fig 3.Systematic evaluation of quality of the ASD phenotype report. Six phenotype experts independently scored eight published reports[100][101][102][103][104][105][106][107] using this algorithm; results indicated 98% consistency regarding the rating of low, medium and high confidence in the reported ASD phenotype, and 90% consistency regarding the cognitive ability information. Proposed scoring adjustments: If default score is 2 (ClinGen default for de novo variant): low confidence (-1) and medium confidence (-0.5); if default score is 1.5 (ClinGen default for an inherited variant that is predicted/proven null): low confidence (-0.5) and medium confidence (-0.25); if default score is 0.5 (ClinGen default for an inherited variant not predicted/proven null, with some evidence of gene impact, e.g.…”
mentioning
confidence: 99%
“…However, these SNPs showed no polymorphism in the CHB population. Recently, one study found that rs10497655 in ZNF804A was significantly associated with ASD (OR = 1.20 (95%CI 1.05–1.37), P = 0.007851) in a Han Chinese cohort (854 cases and 926 controls) and the T risk allele homozygotes of rs10497655 could reduce ZNF804A expression [46]. On the other hand, Griswold et al found duplications of CNVs in ZNF804A only in autistic individuals [47].…”
Section: Discussionmentioning
confidence: 99%